MEMBANGUN GENERASI MELEK LITERASI: OPTIMALISASI TAMAN BACA MASYARAKAT SARAS ALUS DI DESA NYEROT - Alnaziroq, Alni; Jurnal Wicara; Sari, Ni Putu; Pertiwi, Sabrina; Nulhakki, Ikmal; Nurahmaniah, Ingke; Sari, Indah; Rane, M.; Nafilah, Nur; Putri, Widiya; Rizaldi, M.; Nurmayanti, Siti (Universitas Mataram, 2025)
Quality education is expected to create a generation that is able to adapt to challenges. To achieve this, the development of superior human resources must begin with efforts to instill an interest in reading from an early age, both in schools and in the community, so that every individual has equal access to knowledge. This study aims to examine the effectiveness of optimizing the Community Reading Park as an effort to build a literate generation in Nyerot Village. The problem of low interest in reading in the village is a major urgency that must be prioritized by the village government so that it can be addressed immediately. Through the PMD Real Work Lecture activity in Nyerot Village in collaboration with the National Library, a work program focused on literacy was presented. The methods used in this activity were initial observation, preparation, and implementation of activities carried out at the Saras Alus Community Reading Park in Nyerot Village. Various activities were carried out, such as reading aloud, book reviews, and implementing simple projects based on reading books. Through these activities, children not only read, but also experienced learning activities accompanied by play so that it did not feel boring. Additionally, the children who participated in the learning activities at the TBM were very enthusiastic, which helped develop their level of participation in utilizing their free time in a meaningful way.